2018
DOI: 10.1111/bcp.13655
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability and pharmacokinetics/pharmacodynamics of the adrenomedullin antibody adrecizumab in a first‐in‐human study and during experimental human endotoxaemia in healthy subjects

Abstract: Administration of adrecizumab is safe and well tolerated in humans, both in the absence and presence of systemic inflammation. These findings pave the way for further investigation of adrecizumab in sepsis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 41 publications
1
37
0
1
Order By: Relevance
“…Importantly, even though adrecizumab induced great increases in circulating levels of ADM, this did not cause hypotension. In a phase Ib study, where healthy subjects received an infusion of bacterial lipopolysaccharide to induce a systemic inflammatory response, administration of adrecizumab significantly reduced the perception of illness/sickness, as assessed by clinical scores …”
Section: Adrecizumab For the Treatment Of Heart Failure And Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, even though adrecizumab induced great increases in circulating levels of ADM, this did not cause hypotension. In a phase Ib study, where healthy subjects received an infusion of bacterial lipopolysaccharide to induce a systemic inflammatory response, administration of adrecizumab significantly reduced the perception of illness/sickness, as assessed by clinical scores …”
Section: Adrecizumab For the Treatment Of Heart Failure And Sepsismentioning
confidence: 99%
“…In a phase Ib study, where healthy subjects received an infusion of bacterial lipopolysaccharide to induce a systemic inflammatory response, administration of adrecizumab significantly reduced the perception of illness/sickness, as assessed by clinical scores. 73 A phase II proof of concept study in patients with worsening heart failure and elevated bio-ADM levels after initial stabilization is currently being considered. Patients with elevated bio-ADM have (residual) congestion and are at high risk for clinical events, and a heart failure readmission in particular.…”
Section: Adrecizumab For the Treatment Of Heart Failure And Sepsismentioning
confidence: 99%
“…Also, pretreatment with Adrecizumab improved 7-day survival in CLP-induced sepsis in mice from 10 to 50% for single and from 0 to 40% for repeated dose administration ( 151 ). Moreover, in a phase I study, excellent safety and tolerability was demonstrated: no serious adverse events were observed, no signal of adverse events occurring more frequently in Adrecizumab-treated subjects was detected, and no relevant changes in other safety parameters were found ( 152 ). Of particular interest is the proposed mechanism of action of Adrecizumab.…”
Section: Adm and Adm-targeted Therapy As Treatment Strategies Relevanmentioning
confidence: 99%
“…Both animal and human data reveal a potent, dose-dependent increase of circulating ADM following administration of this antibody. Based on pharmacokinetic data and the lack of an increase in MR-proADM (an inactive peptide fragment derived from the same prohormone as ADM), the higher circulating ADM levels cannot be explained by an increased production ( 152 ). A mechanistic explanation for this increase could be that the excess of antibody in the circulation may drain ADM from the interstitium to the circulation, since ADM is small enough to cross the endothelial barrier, whereas the antibody is not.…”
Section: Adm and Adm-targeted Therapy As Treatment Strategies Relevanmentioning
confidence: 99%
“…The loss of vascular integrity plays a pivotal role in the development of vascular leakage and organ dysfunction leading to septic shock [24][25][26]. Several animal studies have proven that ADM shows strong anti-inflammatory properties, improves the cardiomyocyte survival in myocardial ischemia, and has a marked anti-apoptotic effect on cardiomyocytes [27,28].…”
Section: Adrecizumab and Shockmentioning
confidence: 99%